Brazilian Protocol for Sexually Transmitted Infections 2020: human papillomavirus (HPV) infection - Carvalho,Newton Sergio de (2021)
Abstract This article addresses human papillomavirus (HPV) infection, one of the topics covered by the Clinical Protocol and Therapeutic Guidelines for Comprehensive Care for People with Sexually Transmitted Infections, published by the Brazilian Ministry of Health. The Protocol and Guidelines have been developed based on scientific evidence and validated in discussions with specialists. This article presents epidemiological and clinical aspects and guidelines for health service managers and health workers about diagnosing and treating people with papillomavirus infection. This theme is a significant public health issue since it is the most prevalent sexually transmitted infection globally, capable of triggering the oncogenic process of cervical cancer and the possibility of anogenital warts. Important information is presented for gaining knowledge about HPV and action strategies for infection prevention and control, provision of quality care, and effective treatment of the disease.